2014
DOI: 10.1088/0004-637x/784/2/173
|View full text |Cite
|
Sign up to set email alerts
|

C/O Abundance Ratios, Iron Depletions, and Infrared Dust Features in Galactic Planetary Nebulae

Abstract: We study the dust present in 56 Galactic planetary nebulae (PNe) through their iron depletion factors, their C/O abundance ratios (in 51 objects), and the dust features that appear in their infrared spectra (for 33 objects). Our sample objects have deep optical spectra of good quality, and most of them also have ultraviolet observations. We use these observations to derive the iron abundances and the C/O abundance ratios in a homogeneous way for all the objects. We compile detections of infrared dust features … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
42
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 84 publications
8
42
1
Order By: Relevance
“…We adopt C/O=0.87±0.25 from C ii and O ii recombination lines (see Fig 8 and the ICFs given by Kingsburgh & Barlow 1994). C/O ratios from ORLs generally agree with those derived from UV/optical CELs Delgado-Inglada & Rodríguez 2014) and, additionally, they are not affected by aperture corrections and extinction uncertainties, which can potentially affect C/O ratios derived from CELs. Additionally, we also include some data from García-Rojas et al We use PySSN to deblend this line from the charge transfer feature, the telluric emission lines and a close He i line (see Fig.…”
Section: Correlation Of S-process Enrichments With the C/o Ratiomentioning
confidence: 77%
See 1 more Smart Citation
“…We adopt C/O=0.87±0.25 from C ii and O ii recombination lines (see Fig 8 and the ICFs given by Kingsburgh & Barlow 1994). C/O ratios from ORLs generally agree with those derived from UV/optical CELs Delgado-Inglada & Rodríguez 2014) and, additionally, they are not affected by aperture corrections and extinction uncertainties, which can potentially affect C/O ratios derived from CELs. Additionally, we also include some data from García-Rojas et al We use PySSN to deblend this line from the charge transfer feature, the telluric emission lines and a close He i line (see Fig.…”
Section: Correlation Of S-process Enrichments With the C/o Ratiomentioning
confidence: 77%
“…For highly ionized Fe ions, we adopt the data recommended by Delgado-Inglada & Rodríguez (2014), and for neutron-capture elements we use the atomic data references compiled by Sharpee et al (2007). Errors in the line fluxes and the physical conditions were propagated via Monte Carlo simulations.…”
Section: Adopted 6200±1250mentioning
confidence: 99%
“…Obviously, the abundances in both IC4846 and Hen3-1357 are in excellent agreement even in the RL ǫ(C,N,O) and the Fe-depletion. So far, the ǫ(Mg) and ǫ(Fe) measurements have been performed only by Hyung et al (2001) using the IUE UV-spectrum and only by Delgado-Inglada & Rodríguez (2014) using the optical spectra, respectively. The largely depleted [Mg/H] = -1.69 in IC4846 might indicate that most of the Mg-atoms are captured by silicate grains.…”
Section: Discussionmentioning
confidence: 99%
“…This problem is well known in nebular physics and consist in the fact that, for a given ion, ORLs provide systematically higher abundances than those obtained using CELs; this difference is generally parametrized by the abundance discrepancy factor (ADF), which is the ratio between ORLs and CELs abundances. Wang & Liu (2007) and Delgado-Inglada & Rodríguez (2014) showed that when computed simultaneously, ADFs given by N, O and C ions show an overall agreement that translates in very similar N/O and C/O when computed from both CELs and ORLs. With this method we avoid the biases discussed by Rola & Stasińska (1994) as we have computed the abundances from high-signal-to-noise optical spectra and used the same type of lines to compute C and O abundances.…”
Section: Ionic Abundances From Recombination Linesmentioning
confidence: 94%